USER-CENTERED DESIGN IN AGILE SOFTWARE DEVELOPMENT ENVIRONMENTS: COMPARATIVE EVALUATION OF USABILITY TESTING APPROACHES - Nahar, Garima; Bordia Jain, Dr. Sonal (South Eastern European Journal of Public Health, 2025)
The Agile-Software-Development Model firmly emphasizes "learning by doing" and categorically rejects BDUF (Big-Design-Up-Front) [1]. In contrast, UCD (User-Centered Design) adopts a comprehensive approach essential for creating an operational UI (User-Interface), ultimately ensuring an excellent user experience [2]. Achieving an equilibrium between Incremental-Development and a comprehensive view of the user interface is essential for ensuring usability in Agile-Software-Development. This paper establishes a framework for the effective integration of User-Centered Design (UCD) with Agile methodologies, specifically tailored for the web-based tool Antlion optimization (ALO) Algorithm at the Information Systems and Information Technology department of Com Hem AB, a Swedish telecommunications company in Sweden. The findings demonstrate that the successful incorporation of UCD into Agile development demands a shared foundational understanding for both usability developers and experts. Thisone can be effectively accomplished through what author Desirée Sy defines as “Cycle Zero” [3], which enables usability specialists to conduct essential preliminary research prior to execution. By designing one sprint, the process will evolve into a coordinated workflow where interface drafts and requirements are developed collaboratively with developers, precisely when needed for implementation. This strategy not only eliminates unwanted associated with excessive documentation and misperception during hand-offs, but it also enhances the execution process, making it more focused and enjoyable for designers and developers. To achieve a successful development process, it is essential to develop prototypes soon. This approach is necessary to establish a clear and comprehensive vision of the finished product while enabling early usability testing of concepts. Furthermore, it is imperative to create a shared understanding of user needs among both the development team and external stakeholders. Involving the entire team in usability testing is essential for this alignment. Finally, all external stakeholders must grasp the Agile process and recognize that the team operates as a self-organizing unit [4]. This means the team tackles challenges within defined boundaries rather than simply acting as a code factory reliant on specification documents